Los dos mundos: rural Mexican Americans, another America - Baker, Richard, author; Utah State University Press, publisher (Colorado State University. Libraries, 1995)
Mexican Americans make up the largest minority in Idaho, yet they seemingly live in a different world from the dominant Anglo population, and because of pervasive stereotypes and exclusive policies, their participation in the community's social, economic, and political life is continually impeded. This unique ethnographic study of a small Idaho community with a large Hispanic population examines many dimensions of the impact race relations have on everyday life for rural Mexican Americans.
Overview of Field Research and Theoretical Models -- The Anglo Community of Middlewest -- Mexican American Culture and Daily Life -- Mexican American Leaders Defend Their Culture and People -- The Anglo Working Class and Anglo Farmers -- Permanent Working Class Mexicans -- Mexican American Migrant Workers -- Institutionalized Racism as Part of the Exploitive Model -- The Education Institution -- Conclusions and Recommendations.
Keywords: Mexican Americans -- Idaho -- Social conditions; Idaho -- Social conditions